COMPREHENSIVE PAIN MANAGEMENT PHARMACOTHERAPY: A MULTIDISCIPLINARY STRATEGIES AND QUALITY ASSURANCE FOR ENHANCED PATIENT-CENTERED OUTCOME - Bharathraj Masilamani; Kanaka Parvathi Kannaiah; Manimaran V (The Bioscan, 2025)
Pain management is a critical aspect of healthcare in diseased patients, involving the alleviation of both acute and chronic pain through a multidisciplinary approach. Acute pain can often be resolved with direct pharmacological interventions, while chronic pain requires more complex treatment and coordinated efforts. Multidisciplinary teams typically include medical professionals, pharmacists, psychotherapists, and rehabilitation specialists and other healthcare professionals in the setup of the organization. Pain can persist due to ongoing pathology, unresolved trauma, or unidentified causes, necessitating varied treatment strategies such as administration of analgesics, antidepressants, anticonvulsants, physical therapy, and psychological interventions. Effective pain management mainly relies on accurate pain assessment, the chronic pain assessment and the use of quality improvement programs. The Joint Commission for Accreditation of Healthcare Organizations (JCAHO) recognized pain management as critical quality indicator in 1999, incorporating pharmacotherapy as the fifth vital sign and encouraging institutional accountability for the management of pain. Guidelines are developed by agencies such as, the Agency for Healthcare Policy and Research emphasize patient education, prompt pain assessment, and consistent documentation of treatment effectiveness. Developing quality assurance programme for the management of pain and pharmacotherapy by administering drugs of opioids, NSAIDs and other non-opioid medications. Multidisciplinary collaboration to establish various policy guidelines for quality assurance pain management establish policies, train staff, and evaluate program effectiveness. The Case studies highlight the diversity of pain management which needs across patient populations, from the postoperative care to chronic conditions. These cases which demonstrates the necessity of tailored approaches, particularly for managing pain in the elderly patients or those with complex medical conditions. A comprehensive, bio psychosocial rehabilitation approach is emphasized, integrating medical, psychological, and physical therapies to improve patient outcomes and quality of life.